Keefektifan Penggunaan Media Pembelajaran Simulasi Interaktif Berbasis Canva untuk Meningkatkan Hasil Belajar Peserta Didik - Jayanti, Siswi; Sasmita, Febriarsita Eka; Mala, Asnal (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
The difficulty of understanding abstract learning concepts and the lack of learning facilities affect the low learning outcomes of unit of time material. This study aims to determine the effectiveness of learning media in improving the learning outcomes of students in grade III MI / SD. This study uses a quantitative approach with the subjects of students in grades IIIA and IIIB, each consisting of 25 students. Data were collected through observation and learning outcome tests, including pre-test and post-test scores for the experimental and control classes. The results showed that the average pre-test and post-test scores in the experimental class were 66.72 and 94.08, while in the control class they were 63.52 and 91.02. This significant difference proves that the Canva-based interactive simulation learning media is “Effective” in improving the learning outcomes of students on the unit of time material in class III MINU Tambak Sumur, Waru Sidoarjo.